Sistem Pengaman Ruang Aset Berbasis Internet of Things (IoT) Menggunakan Sensor Wajah ESP32-Cam - Wibowo, Dwi Ari; Nugroho, Supriyana; Rahayu, Cicilia Puji (Politeknosains, 2023)
Asset space in an office building is one of the most valuable spaces for a company, for this reason a sophisticated security system must be built using modern technology. In this study, an Internet of Things (IoT) based security system was built using the ESP32-Cam face sensor. The sensor can only detect the face of the person who is responsible for the asset space and the face has been registered in advance with the application. If the sensor detects a face that has been registered, the ESP32-Cam module will send an output signal to the 5 volt relay module, so that the point relay contact which was originally normally open will change to normally close. As a result, the 12 volt voltage from the power supply will be connected to the door lock solenoid, and the lock will open. If the sensor does not detect a face, it means that the face has not been registered with the system, then the asset room door lock will remain locked.